Quantifying the impacts of energy price reform on living expenses in Saudi Arabia - Bah, Muhammad Maladoh; Saari, M. Yusof (Elsevier, 2020)
As part of ‘Vision 2030’, Saudi Arabia has initiated a broad-based energy reform programme aimed at gradually reducing its dependence on oil. This paper assesses the impacts of energy price reforms on living expenses of various household groups in Saudi Arabia. For this purpose, the input-output table combined with household expenditure data are used to model the impacts. Results show that the distributional impacts of energy price reforms are regressive, with low-income households experiencing a higher increase in living expenses compared to high-income households. The impacts are primarily instigated by rising prices of energy-intensive products. After decomposing the impacts into direct and indirect effects, it was found that indirect effect is not only responsible for a considerable rise in household expenditure on energy-intensive products, but it is also distributionally regressive. It is therefore vital for policymakers to review and fine-tune the social protection system to protect poor households against reforms.